Особливості успадкування деяких ознак у сіянців лілійника гібридного (Hemerocallis hybrida hort.) 'Blushing Bell' в першому поколінні - Krokhmal, I.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Peculiarities of morphological development of Hemerocallis hybrida 'Blushing Bell' seedlings in F1 using multifactor regressive analysis were studied. Analytical regression equations for assessment of variability and important breeding characters inheritance allowed determining complementary interaction of genes, which control height of generative shoot, diameter, shape and color of flowers.